Important moments in the training of Khoja Ahmed Yassaui works (Journal of Oriental Studies, 2018)
This article discusses the problems of studying the Sufi religious termsand in the writings of Khoja Ahmed Iassavi and etymology of some wordsborrowed from Arabic.